KEEFEKTIFITASAN AROMATERAPI LAVENDER DALAM MENURUNKAN STRES PADA MAHASISWA KEPERAWATAN TINGKAT AKHIR - Eri Riana Pertiwi; Ratna Juwita (Jurnal Kesehatan Hesti Wira Sakti, 2023)
Introduction: Students are very vulnerable to problems related to academic pressure due to transitions that occur at the individual and social levels. It is estimated that 10-30% of students experience academic stress during their studies at tertiary institutions. This study aims to determine the effectiveness of applying lavender aromatherapy in reducing stress in final-year nursing students. Methods: This research is a quasy experiment with a pre-test and post-test design approach. The population in this study were final year students, totalling 242 people with a total sample of 39 people. The sampling technique used in this study was non-probability sampling. Data processing in this study used the application of SPSS 16. While the data analysis used in this study was statistical analysis. Result Test: the study found that lavender aromatherapy was effective in reducing the stress level of final-year students. During the pre-test measurement, the average value (mean) was 25.53, while the measurement results during the post-test obtained an average value (mean) of 22.23 with a p-value = 0.000. Conclusion: there are differences in the stress level of final-year students before and after being given aromatherapy. Suggestions for future researchers is to conduct research with a quasi-experimental design, to provide 2 different interventions to students in reducing  student stress levels.